Supply Chain Management System Analysis in Improving Product Quality at PT. Kaya Kreasi Indonesia - Irmayani, Ni Wayan Dian (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
The aim of this research is to explain how PT Kaya Kreasi Indonesia's supply chain management system contributes to improving the quality of the company's products due to the process of purchasing and determining fabric raw materials for clothing production in the company which is currently happening in the field, and how to obtain quality raw materials, on time, and in the right quantities until the final product is delivered to consumers. The method used in this research is descriptive qualitative. The data used is primary and secondary. Primary data comes from case studies and research journals as well as objective company data. This study found that supply chain management influences the performance of PT Kaya Kreasi Indonesia, which relates to suppliers, manufacturers and consumers. PT Kaya Kreasi Indonesia shows this good relationship by implementing ISO quality assurance, which provides confidence to buyers and suppliers during the product export process. Several factors, such as weather, human resources, production and delivery delays, are obstacles in PT Kaya Kreasi Indonesia's supply chain management. PT Kaya Kreasi Indonesia also has several ways to handle these challenges.